Optimization of the Management Process in Conditions of the Political Space Transformation: Methodology of Conflict Analysis - YURCHENKO, Natalia; SKOROBOGATOV, Viktor; YURCHENKO, Inna; DONTSOVA, Mariya; TELYATNIK, Tatiana (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).38, 2018)
The problematic area of this article relates to the current direction of research searching for optimal management tools in the context of global changes in the geopolitical and economic space, as well as large-scale migration. The existing conditions have an extremely high conflict-generating potential, which requires the development of effective tools to stabilize and monitor the situation, to seek ways of civilized resolution of conflicts and contradictions. The purpose of the article is the identification of mechanisms for optimizing the management process in the context of the transformation of the conflict political space. The authors of the article suggest an innovative approach to the analysis of the phenomenon of transformation of political space at the superstructure level, using a conflict paradigm, as well as systemic and structural-functional approaches. For a productive way of studying management technologies in the context of the transformation of political space, a frame analysis is proposed that allows observing the dynamics of events, including the results of management practices, in the form of a temporary event matrix and a generalized scheme of interpretations by the observer. The article presents in detail the well-known and new scientific directions dealing with the problems of effective political management, the optimization of the mechanisms for political decision-making, diagnosis, resolution and prevention of conflicts in the socio-economic, ethno-political and other areas, through a comprehensive analysis of the conflictogenesis of a modern socio-political subject. The authors of the article come to the conclusion that the political-administrative elite, the mass media determine the thematization of political-administrative discourse, the dominance in the political media space and the replication of new meanings and symbols. Mechanisms for optimizing the management process, therefore, should be based on developing technologies for managing political risks and emerging spontaneous changes, taking into consideration the presence of unregulated, natural, yet reportable interactions in the sphere of politics, economics and social communications.